Arbitration Agreement to Non-Signatory Parties in Indonesia - Herwinda Rena Damayanti; Alifah Sarah Yunita; Mega Lois Aprilia (Notaire, 2019)
AbstractInternational business transaction, especially in the exchange of goods and services nowadays, a contract is normally concluded to govern the entire relation between the parties. Ideally, the perfect contract probably should be able to give foresights to all possible scenarios and their solutions, regarding the beginning of the business relationship, its performance and finally its termination. In today’s commercial transaction, the parties will draw up an arbitration agreement in their contract to submit all disputes arising from a contract to a neutral body. The presence of non-signatories party in arbitration agreement is apparent on a contract which involves an affiliated companies. This situation arises because it is becoming more acceptable nowadays for a company to establish subsidiary companies in order to make business transaction become more swift and sophisticated. The liability issue normally happened when there are two company that are affiliated to each other while only one of them signed the contract. On this ground, there have been some cases wherein the affiliation is considered as an equal liability between the parent company and subsidiary, especially when the parent company is also involved in the contract performance. Extending the scope of an arbitration agreement to a party who is initially not signed under the agreement would defeat the original purpose of having the agreement in the first place. It must be remembered that the starting point of arbitration agreement is its privity, that is, it will only bind the parties who signed it From this perspective, a question arises on whether according to the regulations in Indonesia, an action of a company who has knowingly engage themselves in a contract concluded by their affiliates will make them bound to the contract and the arbitration agreement as well. This research is to give a better understanding on to what extent does a company, who only acts as a non-signatory, can be bound to an arbitration agreement if a dispute arises by seeing it from the Indonesian law perspective.